Evaluate the following using compound angle formulae:

`tan (-Pi/4 - Pi/6)`

### 1 Answer | Add Yours

Evaluate `tan(-pi/4 - pi/6)` :

Use `tan(A-B)=(tanA-tanB)/(1+tanAtanB)`

where `A=-pi/4,tanA=-1,B=pi/6,tanB=1/sqrt(3)`

`tan(-pi/4-pi/6)=(tan(-pi/4)-tan(pi/6))/(1+tan(-pi/4)tan(pi/6))`

`=(-1-1/sqrt(3))/(1+(-1)(1/sqrt(3)))`

`=(-1-1/sqrt(3))/(1-1/sqrt(3))*sqrt(3)/sqrt(3)`

`=(-sqrt(3)-1)/(sqrt(3)-1)`

`=(-sqrt(3)-1)/(sqrt(3)-1)*(sqrt(3)+1)/(sqrt(3)+1)`

`=(-4-2sqrt(3))/2`

`=-2-sqrt(3)`

----------------------------------------------------------

`tan(-pi/4-pi/6)=-2-sqrt(3)~~-3.73`

----------------------------------------------------------

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes